Hydrogen gettering in annealed oxygen-implanted silicon - Misiuk, A.; Barcz, A.; Ulyashin, A.; Antonova, I.V.; Prujszczyk, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Hydrogen gettering by buried layers formed in oxygen-implanted silicon (Si:O
prepared by O²⁺ implantation at the energy 200 keV and doses 10¹⁴ and 10¹⁷ cm⁻²) was
investigated after annealing of Si:O at temperatures up to 1570 K, including also
processing under enhanced hydrostatic pressure, up to 1.2 GPa. Depending on processing
conditions, buried layers containing SiO₂₋x clusters and/or precipitates were formed. To
produce hydrogen-rich Si:O,H structures, Si:O samples were subsequently treated in RF
hydrogen plasma. As determined using secondary ion mass spectrometry, hydrogen was
accumulated in sub-surface region as well as within implantation-disturbed areas. It has
been found that hydrogen was still present in Si:O,H structures formed by oxygen
implantation with the dose D = 10⁷ cm⁻² even after post-implantation annealing up to
873 K. It is concluded that hydrogen accumulation within the disturbed areas in Si:O as
well as in SOI structures can be used for recognition of defects.